Poštivanje autorskih prava pri uporabi psihologijskih testova - Matešić, Krunoslav (Array, 2014)
Psychological tests are divided into research instruments and psychodiagnostic instruments. The latter, when newly developed, usually constitute independent publications, produced by test publishers as a core activity. Despite the fact that many research instruments are in the so- called public domain, there are still versions published in journals which require full copyright acknowledgement. Following the Psychological Practice Act (NN 88/2003), the Croatian Psychological Chamber has accepted the A-B-C categorization model for the classification of existing psychological instruments. The laws of the Republic of Croatia forbid the unauthorized copying of psychological instruments. However, awareness of the need to respect publication and authorship rights has been slow to develop. Numerous journals are publishing papers presenting results of illegally acquired instruments. A series of professional associations have stablished numerous standards, guidelines, recommendations and statements regarding psychological testing practices and protection of the actual tests, with the aim of improving the quality of psychological practice, protection of test subject rights as well as the protection of moral and material rights of the author and test publisher. The International Test Commission has initiated a public discussion regarding research instruments, see ww.intestcom.org/upload/ statement_on_tests_for_research_20131203.pdf. The proper use of research instruments and psychodiagnostic tests can be achieved through education and active interaction in the academic community in order to explain all aspects of copyrights.